2017
DOI: 10.1002/jcb.25841
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation: Causes and Consequences in Skeletal Muscle Myopathy

Abstract: A detrimental consequence of hypermethylation is hyperhomocysteinemia (HHcy), that causes oxidative stress, inflammation, and matrix degradation, which leads to multi-pathology in different organs. Although, it is well known that hypermethylation leads to overall gene silencing and hypomethylation leads to overall gene activation, the role of such process in skeletal muscle dysfunction during HHcy condition is unclear. In this study, we emphasized the multiple mechanisms including epigenetic alteration by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 104 publications
(190 reference statements)
0
35
0
Order By: Relevance
“…There are also several other drivers like age, sex, physical activity, alcohol intake, certain medications, and different disease conditions (such as type 2-diabetes) that can also modulate the functioning Met cycle leading to an increased total Hcy concentration in the blood (Diakoumopoulou et al 2005). Hyperhomocysteinemia (HHcy) has been associated with severe skeletal muscle dysfunction (Brustolin et al 2010;Kanwar et al 1976;Kolling et al 2013;Majumder et al 2017;Miller et al 2000;Valentino et al 2010;Veeranki et al 2015;Voskoboeva et al 2018;Zoccolella et al 2008), but the precise mechanism(s) is still unknown. Previous studies found that HHcy causes endothelial cell (EC) injury (Wang et al 1997), inhibition of EC proliferation (Zou et al 2011), reduction of bioavailability of vasoregulatory mediators (nitric oxide and endothelin) (Upchurch et al 1997), and induction of oxidative/ER-stress Tyagi et al 2005;Werstuck et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There are also several other drivers like age, sex, physical activity, alcohol intake, certain medications, and different disease conditions (such as type 2-diabetes) that can also modulate the functioning Met cycle leading to an increased total Hcy concentration in the blood (Diakoumopoulou et al 2005). Hyperhomocysteinemia (HHcy) has been associated with severe skeletal muscle dysfunction (Brustolin et al 2010;Kanwar et al 1976;Kolling et al 2013;Majumder et al 2017;Miller et al 2000;Valentino et al 2010;Veeranki et al 2015;Voskoboeva et al 2018;Zoccolella et al 2008), but the precise mechanism(s) is still unknown. Previous studies found that HHcy causes endothelial cell (EC) injury (Wang et al 1997), inhibition of EC proliferation (Zou et al 2011), reduction of bioavailability of vasoregulatory mediators (nitric oxide and endothelin) (Upchurch et al 1997), and induction of oxidative/ER-stress Tyagi et al 2005;Werstuck et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In our study we present for the first time changes of the synaptic transmission during postnatal development in rat neuromuscular junction caused by elevated levels of the endogenous amino acid HCY during the prenatal period. Several previous studies reported that an increased level of HCY leads to functional impairments and weakness of skeletal muscle (Veeranki and Tyagi, 2013; Ng et al, 2012; Swart et al, 2013; Majumder et al, 2017, 2018a,b). Children born with severe homocystinuria due to CBS deficiency exhibit low body weight and skeletal muscle myopathy (Picker and Levy, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, using a spectrophotometric assay we found an increase of H 2 O 2 level and lipid peroxidation in muscles of neonatal and adult rats in the hHCY group. Apparently, this increased level of ROS can cause oxidation of various functionally important proteins, including the presynaptic transmitter releasing machinery which is the most redox‐sensitive part of the motor synapse (Giniatullin et al, 2006; Majumder et al, 2017; Veeranki and Tyagi, 2013) and as a result causes the functional changes of neuromuscular synapses in hHCY.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations